Variasi Harga Jual Gelembung Ikan oleh Nelayan Lampu Satu di Kabupaten Merauke - Sajriawati Sajriawati (Musamus Journal of Agribusiness, 2020)
Research about price variations of fish maw by fisherman in Lampu Satu Merauke Districts aims to determine variations in the price of fish maw and the determining factors for these price variations. This research was conducted in Merauke District for 2 (two) months from June to July 2020, using survey methods and interviews with fishermen. The object of this research is 5 fishermen who do fish maw fishing activities in MeraukeDistrict. The data analysis used is descriptive analysis, namely data analysis in the form of research reports in writing as well as pictures and tables. The results showed that the price variations of fish maw by fisherman in Lampu Satu Merauke Districts was determined by the type of fish, the sex of the fish, and the classification of the weight of the fish maw. The heavier the fish maw, the more expensive the selling price per kg. The price of fish maw for Gulama is higher than that of fish maw from Chinese snapper, while the price for fish maw from male Chinese snapper is higher than that fish maw from female Chinese snapper. Keywords: Price variations, fish maw, Merauke District